2010
DOI: 10.1002/pssb.200983955
|View full text |Cite
|
Sign up to set email alerts
|

Exciton‐polaritons in microcavities: Recent discoveries and perspectives

Abstract: The exciton-polaritons in microcavities is a unique bosonic system which demonstrates remarkable quantum coherent phenomena at very high temperatures. The Bose-Einstein condensation (BEC) and superfluidity, polariton lasing, parametric scattering and amplification, polariton spin switching, optical spin Hall effect (OSHE), quantised vortices are among the fascinating phenomena discovered in microcavities in the XXIst century. This paper is a short review of these and other recent discoveries in the exciton-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…1,2 In the past ten years, it has been shown that MC polaritons can be useful in a number of optoelectronic device applications as well as fundamental studies. [3][4][5][6][7] The in-plane propagation of polaritons has also recently attracted a considerable research effort: superfluid behavior of MC polaritons has been demonstrated in their coherent state 8 while bistable switching of polariton waves has been proposed as a way to achieve optical logical gates. 9 Various strategies to guide the propagation of polaritons have been theoretically proposed or experimentally demonstrated, including wire MCs, 10 or the use of metallic deposition and the creation of hybrid Tamm-like exciton-polariton states.…”
mentioning
confidence: 99%
“…1,2 In the past ten years, it has been shown that MC polaritons can be useful in a number of optoelectronic device applications as well as fundamental studies. [3][4][5][6][7] The in-plane propagation of polaritons has also recently attracted a considerable research effort: superfluid behavior of MC polaritons has been demonstrated in their coherent state 8 while bistable switching of polariton waves has been proposed as a way to achieve optical logical gates. 9 Various strategies to guide the propagation of polaritons have been theoretically proposed or experimentally demonstrated, including wire MCs, 10 or the use of metallic deposition and the creation of hybrid Tamm-like exciton-polariton states.…”
mentioning
confidence: 99%
“…[1,2] Recently, polariton excitations in two-dimensional geometries have been attracting considerable interest, both for fundamental studies on out-of-equilibrium Bose-Einstein condensation and superfluidity, [3][4][5] and for the possibility to exploit their nonlinear properties for all-optical operations. [6,7] Elementary excitations can be observed in materials such as squaraine, porphyrin and cyanine dyes.…”
mentioning
confidence: 99%
“…In 1992, it had been experimentally demonstrated by Weisbuch et al [208], that, in the strong coupling regime the interaction between the exciton state in semiconductor and confined light mode in the microcavity can lead to the formation of completely two new eigenstates which have different properties than the bare exciton or the photon states. These collective excitation comprising part-light part-matter quasiparticles are known as exciton polaritons [209]. [211,212].…”
Section: Introductionmentioning
confidence: 99%